Aqueous organic zinc ion battery positive pole piece, preparation method thereof and aqueous organic zinc ion battery prepared from aqueous organic zinc ion battery positive pole piece
By using BBOPO as the positive electrode material in the aqueous zinc ion battery and combining the coating method of conductive agent and binder, the existing lithium-ion battery resources are solved and the problem of insufficient performance of the positive electrode material of the aqueous zinc ion battery under high current density is achieved, and a water-based organic zinc ion battery with high safety, good circulation performance and low cost is achieved.
Patent Information
- Application Number
- CN202411791907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In the future development of existing lithium-ion batteries, there are problems with limited lithium resources, high costs and safety of organic electrolytes. Water-based zinc-ion batteries have attracted attention due to their high safety, low cost and environmental friendliness, but the existing positive electrode materials have low cycling stability and charging and discharging efficiency under high current density.
3,3'-bis[1,4]benzooxazine[2,3,4-KL]phenozoazine (BBOPO) was used as the positive electrode organic active substance, combined with a conductive agent and a binder, and a positive electrode sheet was prepared by coating to form an aqueous organic zinc ion battery.
It has achieved high safety, good cycling performance under high current density, high charging and discharge window, low production costs and environmental friendliness, and rich materials and high global zinc resource reserves.
Smart Images

Figure CN119786504A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc ion batteries, and mainly relates to an aqueous organic zinc ion battery positive electrode sheet and a preparation method thereof, and an aqueous organic zinc ion battery made thereof. Background Art
[0002] Although high energy density lithium-ion batteries (LIBs) currently dominate the commercial rechargeable battery market, the limited lithium resources, high cost and safety issues of organic electrolytes restrict their further development. Aqueous zinc-ion batteries (ZIBs) have attracted attention for their aqueous electrolytes, low cost, environmental friendliness and high safety. Zinc metal is an ideal negative electrode material due to its high theoretical capacity (820mAh / g) and low redox potential (-0.76V vs SHE). ZIBs are considered to be an ideal green battery system due to their high power density, easy preparation and low cost.
[0003] Among the cathode materials of ZIBs, common ones include traditional inorganic materials such as manganese-based oxides, vanadium-based compounds, Prussian blue, and organic compounds. These materials can achieve Zn 2+ Organic compounds are valued for their high discharge specific capacity, high discharge platform, structural diversity and adjustability. Electrochemical performance, resource renewability and environmental friendliness can be optimized by changing the molecular structure.
[0004] In terms of the process preparation of organic cathode materials, organic cathode materials show unique advantages in aqueous zinc-ion batteries compared with inorganic materials. Although inorganic materials such as functional glass and catalytic and environmentally friendly ceramics play an irreplaceable role in specific fields, in the field of batteries, the adjustability and environmental friendliness of organic materials make them more attractive. The multiple active centers and low "dead mass" of organic materials give them great theoretical specific capacity and actual capacity. Although their voltage is low, their performance can be significantly improved by optimizing the structure and preparation process.
[0005] In the prior art, there are several reports on using aromatic heterocyclic materials as positive electrode materials. However, the positive electrode materials in the prior art often have problems such as relatively dispersed free radical electrons, more free radical side reactions, or insufficient structural stability after oxidation, resulting in poor cycle stability of the zinc battery prepared therefrom and low charge and discharge efficiency at high current density.
[0006] Therefore, the development of high-performance organic cathode materials can not only meet the development needs of future energy storage technology, but also play an important role in electric vehicles, large-scale energy storage and portable electronic devices. Through continuous material innovation and process optimization, organic cathode materials are expected to become a key component of future energy storage technology.
[0007] In summary, it is necessary to develop a new technical solution to solve the defects and shortcomings in the existing technology. Summary of the invention
[0008] In order to solve the above-mentioned problems of lithium batteries in future development, the present invention proposes an aqueous organic zinc ion battery positive electrode sheet and a preparation method thereof and an aqueous organic zinc ion battery made thereof. The battery adopts 3,3'-di[1,4]benzoxazine[2,3,4-KL]phenoxazine (BBOPO) as the positive electrode organic active material, combines a conductive agent and a binder, and prepares the positive electrode sheet by a coating method. The specific steps include mixing, grinding, coating, drying, rounding and assembly. The aqueous zinc ion battery prepared by the present invention has high safety, good cycle performance at a large current density (3A / g), high charge and discharge window, low preparation cost and environmental friendliness. In addition, the content of the materials for preparing the battery is very rich in nature, especially the reserves of zinc ore in the world are about 230 million tons. The present invention has development prospects in the fields of future energy storage, 3C equipment power supply and power equipment power supply.
[0009] One object of the present invention is to provide an aqueous organic zinc ion battery positive electrode sheet, the aqueous organic zinc ion battery positive electrode sheet comprising a current collector and a positive electrode active layer disposed on the current collector;
[0010] The positive electrode active layer is composed of positive electrode organic active material, conductive agent and binder;
[0011] The positive electrode organic active material is 3,3'-di[1,4]benzoxazine[2,3,4-KL]phenoxazine.
[0012] Figure 1 The molecular structure of the positive electrode organic active material BBOPO is shown.
[0013] Furthermore, the conductive agent is selected from one or more of carbon black (CB), graphene, acetylene black (ACET) or Ketjen black (KB).
[0014] Furthermore, the binder is selected from one or more of PTFE and PVDF.
[0015] Furthermore, the current collector is selected from one or more of carbon cloth, titanium mesh or stainless steel mesh.
[0016] Furthermore, the mass ratio of the positive electrode organic active material, the conductive agent and the binder is 1:(0.5-1.5):(0.1-1).
[0017] Another object of the present invention is to provide a method for preparing the above-mentioned aqueous organic zinc ion battery positive electrode sheet, comprising the following steps:
[0018] S1. Blending the positive electrode organic active material, the conductive agent and the binder, and grinding them evenly to obtain a slurry;
[0019] S2, coating the slurry on a current collector to form a positive electrode active layer, heating and drying, and then cutting to obtain a positive electrode sheet for an aqueous organic zinc ion battery.
[0020] Furthermore, in step S1, the grinding time is 5-60 min.
[0021] Furthermore, in step S2, the coating method is selected from one or more of wet coating, roller coating, extrusion or dip coating.
[0022] Furthermore, in step S2, the coating loading range is 0.5-20 mg / cm 2 .
[0023] Furthermore, in step S2, the heating temperature is 45-200°C, and the drying time is 30-3600 min.
[0024] Another object of the present invention is to provide an aqueous organic zinc ion battery containing the aqueous organic zinc ion battery positive electrode sheet, wherein the aqueous organic zinc ion battery is a multilayer structure.
[0025] Among them, the negative electrode sheet, the separator, and the positive electrode sheet are in a sandwich structure;
[0026] The electrolyte exists between the positive electrode plate and the negative electrode plate, and the separator is completely soaked by the electrolyte.
[0027] Furthermore, the aqueous organic zinc ion battery has a multilayer structure, which includes, from top to bottom: a negative electrode shell, a negative electrode plate, a separator, a positive electrode plate, a gasket, a washer, and a positive electrode shell.
[0028] Furthermore, the negative electrode plate is a polished zinc plate.
[0029] Furthermore, the negative electrode plate is a 100% pure zinc plate polished by sandpaper, and the mesh number of the sandpaper is 800-2000 meshes.
[0030] Furthermore, the electrolyte is selected from one or more of zinc sulfate (ZnSO4) solution, zinc trifluoromethanesulfonate (Zn(OTF)2) solution or zinc chloride (ZnCl2) solution.
[0031] Furthermore, the concentration of the electrolyte is 0.5-8M.
[0032] Furthermore, the diaphragm is glass fiber.
[0033] The present invention has the following beneficial effects:
[0034] (1) The present invention provides an aqueous organic zinc ion battery positive electrode plate, a preparation method thereof, and an aqueous organic zinc ion battery made thereof. In the aqueous organic zinc ion battery positive electrode plate, an organic material 3,3'-di[1,4]benzoxazine[2,3,4-KL]phenoxazine (BBOPO) is used as the positive electrode organic active substance. BBOPO is a fused heterocyclic compound. Due to the presence of lone pairs of electrons, heteroatoms such as N or O are considered to be redox active parts, which provide active sites in the BBOPO reaction process and show good electrochemical activity. In addition, systematic redox chemistry studies have shown that the oxidized BBOPO ·+ The radical electrons are mainly gathered around N and O atoms and further delocalized into the whole conjugated structure, which has a great impact on the radical species BBOPO. ·+ The stability of BBOPO plays an important role, reducing the occurrence of free radical side reactions, not easily decomposing at high current density, and having good reversibility of electrochemical reactions. In addition, the molecular structure of BBOPO is centrosymmetric, and even exhibits better structural stability and enhanced aromaticity after oxidation, indicating that it has advantages in battery cycle stability, so that the battery containing the zinc ion battery positive electrode material can have both high capacity at high current density and long cycle high capacity retention rate. At the same time, during charging and discharging, the active site (O) of BBOPO can couple with zinc ions to form coordination bonds, and it has 4 active sites, which can provide considerable capacity at high current density. Secondly, its large benzene ring / condensed ring can inhibit the degradation of the cycle process, thereby further enhancing the cycle stability of zinc batteries and the charge and discharge efficiency at high current density.
[0035] (2) Great safety: The aqueous organic zinc ion batteries of the present invention use aqueous solutions as electrolytes, which makes them superior to lithium ion batteries in terms of safety. Due to their extremely high safety, aqueous zinc batteries have lower risks during operation and storage, avoiding potential safety hazards such as high temperatures and combustion that may occur in lithium ion batteries, which is particularly important for large-scale energy storage applications.
[0036] (3) High capacity retention rate at high current density: The aqueous organic zinc ion battery of the present invention has excellent electrochemical performance, and can achieve faster charging and discharging while maintaining a higher battery capacity. Experiments show that the battery using the new material can still be stably charged and discharged at high current density, and the loss of capacity retention rate is small. It can be charged / discharged to the target power in a short time, while it takes longer than traditional materials, which greatly enhances the battery's charge and discharge performance.
[0037] (4) Cost-effectiveness: Although the aqueous organic zinc ion battery of the present invention provides the above-mentioned performance advantages, its production cost is not significantly increased compared with traditional batteries. What is more, the total reserves of zinc resources in the world are much higher than the reserves of lithium resources in the world, which provides raw material guarantees for the large-scale application of zinc ion batteries. In addition, the production process of aqueous zinc batteries is simple and can be assembled in the air, which may be more cost-effective after large-scale production.
[0038] (5) Better environmental performance: The aqueous organic zinc ion battery of the present invention uses an environmentally friendly electrolyte, which reduces pollution to the environment. Compared with the nickel, cobalt, fluorine pollution, organic matter, dust, acid and alkali pollution caused by lithium batteries, the zinc ion battery has lower toxicity. The organic materials used are all degradable, which causes less pollution to the ecological environment. The discarded batteries can also be better recycled and processed, making it an ideal environmentally friendly battery.
[0039] (6) Solution scalability: The method of the present invention has good solution scalability and can be adjusted and optimized according to different application requirements. For different types and structures of positive electrode organic active materials, the performance of zinc batteries can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The molecular structure of the positive electrode organic active material BBOPO is shown.
[0041] Figure 2 Shown is the assembly structure diagram of the aqueous organic zinc ion battery.
[0042] Figure 3 The cycle performance diagram of the aqueous organic zinc ion battery prepared in Application Example 1 is shown.
[0043] Figure 4 The cycle performance diagram of the aqueous organic zinc ion battery prepared in Application Example 2 is shown.
[0044] Figure 5 The rate performance diagram of the aqueous organic zinc ion battery prepared in Application Example 1 is shown.
[0045] Figure 6 The rate performance diagram of the aqueous organic zinc ion battery prepared in Application Example 2 is shown. DETAILED DESCRIPTION
[0046] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0047] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0048] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that vary depending on the desired properties to be obtained by the present invention.
[0049] Example 1
[0050] A positive electrode sheet for an aqueous organic zinc ion battery, the positive electrode sheet for an aqueous organic zinc ion battery comprising a current collector carbon cloth and a positive electrode active layer arranged on the carbon cloth;
[0051] The positive electrode active layer is composed of positive electrode organic active material BBOPO, conductive agent graphene and binder PTFE.
[0052] The method for preparing the above-mentioned aqueous organic zinc ion battery positive electrode sheet comprises the following steps:
[0053] S1. Blend BBOPO, graphene and PTFE (BBOPO: graphene: PTFE = 2:2:1, m / m / m), grind evenly for 30 min to obtain a slurry;
[0054] S2. The slurry is coated on the carbon cloth by wet coating to form a positive electrode active layer with a loading of 10 mg / cm 2 ; Place in a drying oven and dry at 80°C for 360 minutes, then cut and slice to obtain the positive electrode sheet of the aqueous organic zinc ion battery.
[0055] Example 2
[0056] A positive electrode plate for an aqueous organic zinc ion battery, comprising a current collector titanium mesh and a positive electrode active layer arranged on the titanium mesh;
[0057] The positive electrode active layer is composed of positive electrode organic active material BBOPO, conductive agent graphene and binder PTFE.
[0058] The method for preparing the above-mentioned aqueous organic zinc ion battery positive electrode sheet comprises the following steps:
[0059] S1. Blend BBOPO, graphene and PTFE (BBOPO: graphene: PTFE = 2:2:1, m / m / m), grind evenly for 30 min to obtain a slurry;
[0060] S2. The slurry is coated on the titanium mesh by wet coating to form a positive electrode active layer with a loading of 10 mg / cm 2 ; Place in a drying oven and dry at 60°C for 480 minutes, then cut and slice to obtain the positive electrode sheet of the aqueous organic zinc ion battery.
[0061] Application Example 1
[0062] An aqueous organic zinc ion battery containing the aqueous organic zinc ion battery positive electrode plate prepared in Example 1, wherein the aqueous organic zinc ion battery has a multilayer structure, and comprises from top to bottom: a negative electrode shell, a negative electrode plate, a diaphragm, a positive electrode plate, a gasket, a washer, and a positive electrode shell.
[0063] Among them, the negative electrode sheet, the separator, and the positive electrode sheet are in a sandwich structure;
[0064] The electrolyte exists between the positive electrode sheet and the negative electrode sheet, and the separator is completely soaked by the electrolyte;
[0065] The negative electrode plate is a 100% pure zinc plate polished by 1000-grit sandpaper; the diaphragm is glass fiber; and the electrolyte is a Zn(OTF)2 aqueous solution with a concentration of 3M.
[0066] The preparation method of the aqueous organic zinc ion battery comprises the following steps:
[0067] The negative electrode shell, negative electrode plate, diaphragm, positive electrode plate, gasket, washer and positive electrode shell are assembled from top to bottom. When assembling the diaphragm, electrolyte is injected to completely soak the diaphragm. After the assembly is completed, it is squeezed and sealed by a battery press to obtain an aqueous organic zinc ion battery.
[0068] Figure 2 Shown is the assembly structure diagram of the aqueous organic zinc ion battery.
[0069] Application Example 2
[0070] An aqueous organic zinc ion battery containing the aqueous organic zinc ion battery positive electrode plate prepared in Example 2, wherein the aqueous organic zinc ion battery has a multilayer structure, and comprises from top to bottom: a negative electrode shell, a negative electrode plate, a diaphragm, a positive electrode plate, a gasket, a washer, and a positive electrode shell.
[0071] Among them, the negative electrode sheet, the separator, and the positive electrode sheet are in a sandwich structure;
[0072] The electrolyte exists between the positive electrode sheet and the negative electrode sheet, and the separator is completely soaked by the electrolyte;
[0073] The negative electrode plate is a 100% pure zinc plate polished by 1000-grit sandpaper; the diaphragm is glass fiber; and the electrolyte is a Zn(OTF)2 aqueous solution with a concentration of 3M.
[0074] The preparation method of the aqueous organic zinc ion battery comprises the following steps:
[0075] The negative electrode shell, negative electrode plate, diaphragm, positive electrode plate, gasket, washer and positive electrode shell are assembled from top to bottom. When assembling the diaphragm, electrolyte is injected to completely soak the diaphragm. After the assembly is completed, it is squeezed and sealed by a battery press to obtain an aqueous organic zinc ion battery.
[0076] Test Case
[0077] The aqueous organic zinc ion battery prepared in Application Example 1-2 was placed in an electrochemical workstation to test the electrical performance of the battery.
[0078] Test method:
[0079] Battery cycle performance: Set the working order: static, constant current charge, constant current discharge, set the current density to 3A / g, and set the number of cycles to 500.
[0080] Battery rate performance: Set multiple groups of working sequences: static, constant current charging, constant current discharging, set the current density of each group to 0.5A / g, 1A / g, 1.5A / g, 2A / g, 2.5A / g, 3A / g, 4A / g, 5A / g, set the number of cycles for each group to 10.
[0081] The battery cycle performance test results are shown in Table 1. Figure 3 The cycle performance diagram of the aqueous organic zinc ion battery prepared in Application Example 1 is shown; Figure 4 The cycle performance diagram of the aqueous organic zinc ion battery prepared in Application Example 2 is shown.
[0082] Table 1 Battery cycle performance test results of application example 1-2
[0083]
[0084] From Table 1 and Figure 3 It can be seen that the charge-discharge specific capacity of the battery prepared in Application Example 1 reaches a maximum of 116.34 mAh / g. After 500 cycles of charge-discharge, the charge-discharge specific capacity of the battery is still 105.5 mAh / g, and the capacity retention rate is 90.7%. Figure 4It can be seen that the charge and discharge specific capacity of the battery prepared in Application Example 2 reached a maximum of 97.5 mAh / g. After 500 cycles of charge and discharge, the charge and discharge specific capacity of the battery was still 94.4 mAh / g, and the capacity retention rate was 96.8%. It can be seen that the use of BBOPO material as the active material of the battery positive electrode can effectively enhance the cycle stability of the battery.
[0085] The battery rate performance test results are shown in Table 2. Figure 5 The rate performance diagram of the aqueous organic zinc ion battery prepared in Application Example 1 is shown; Figure 6 The rate performance diagram of the aqueous organic zinc ion battery prepared in Application Example 2 is shown.
[0086] Table 2 Application Example 1-2 Battery rate performance test results
[0087]
[0088] From Table 2 and Figure 5 It can be seen that the charge and discharge specific capacity of the battery prepared in Application Example 1 is 117.72mAh / g, 116.59mAh / g, 110.59mAh / g, 107.49mAh / g, 104.93mAh / g, 102.86mAh / g, 100.24mAh / g, and 98.17mAh / g on average at a series of high-rate current densities of 0.5A / g, 1A / g, 1.5A / g, 2A / g, 2.5A / g, 3A / g, 4A / g, and 5A / g. Because BBOPO is a condensed-ring macromolecule, it exhibits a low coulombic efficiency at a low current density, but its activity gradually increases with the increase of current density, and the coulombic efficiency remains at 99%. From the above test results, it can be seen that the battery's charge and discharge specific capacity does not suffer much loss at a larger current density. Even in the last 10 cycles at a current density of 0.5A / g, the average charge and discharge specific capacity is still 118.98mAh / g, with basically no capacity loss, demonstrating the battery's excellent charge and discharge reversibility and its extremely high charge and discharge efficiency at high current density.
[0089] From Table 2 and Figure 6It can be seen that the charge and discharge capacity of the battery prepared in Application Example 2 is 96.49mAh / g, 92.58mAh / g, 88.46mAh / g, 85.96mAh / g, 84.32mAh / g, 83.01mAh / g, 81.12mAh / g, 79.7mAh / g at a series of high-rate current densities of 0.5A / g, 1A / g, 1.5A / g, 2A / g, 2.5A / g, 3A / g, 4A / g, and 5A / g, and the coulomb efficiency remains at 99%. From the above test results, it can be seen that the charge and discharge capacity of the battery does not have much loss at a larger current density, and even the average charge and discharge capacity at a current density of 0.5A / g in the last 10 cycles is still 96.63mAh / g, and there is basically no capacity loss, showing the excellent charge and discharge reversibility of the battery and the extremely high charge and discharge efficiency of the battery at a high current density.
[0090] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0091] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A positive electrode sheet for an aqueous organic zinc ion battery, characterized in that: The aqueous organic zinc ion battery positive electrode plate comprises a current collector and a positive electrode active layer arranged on the current collector; The positive electrode active layer is composed of positive electrode organic active material, conductive agent and binder; The positive electrode organic active material is 3,3'-di[1,4]benzoxazine[2,3,4-KL]phenoxazine.
2. The aqueous organic zinc ion battery positive electrode sheet according to claim 1, characterized in that: The conductive agent is selected from one or more of carbon black, graphene, acetylene black or Ketjen black.
3. The aqueous organic zinc ion battery positive electrode sheet according to claim 1, characterized in that: The binder is selected from one or more of PTFE and PVDF.
4. The aqueous organic zinc ion battery positive electrode sheet according to claim 1, characterized in that: The current collector is selected from one or more of carbon cloth, titanium mesh or stainless steel mesh.
5. The aqueous organic zinc ion battery positive electrode sheet according to claim 1, characterized in that: The mass ratio of the positive electrode organic active material, the conductive agent and the binder is 1:(0.5-1.5):(0.1-1).
6. The method for preparing the positive electrode sheet of an aqueous organic zinc ion battery according to any one of claims 1 to 5, characterized in that: The steps include: S1. Blending the positive electrode organic active material, the conductive agent and the binder, and grinding them evenly to obtain a slurry; S2, coating the slurry on a current collector to form a positive electrode active layer, heating and drying, and then cutting to obtain a positive electrode sheet for an aqueous organic zinc ion battery.
7. The method for preparing the positive electrode sheet of an aqueous organic zinc ion battery according to claim 6, characterized in that: In step S2, the heating temperature is 45-200°C, and the drying time is 30-3600 min.
8. An aqueous organic zinc ion battery comprising the aqueous organic zinc ion battery positive electrode sheet according to any one of claims 1 to 5, characterized in that: The aqueous organic zinc ion battery has a multilayer structure. Among them, the negative electrode sheet, the separator, and the positive electrode sheet are in a sandwich structure; The electrolyte exists between the positive electrode plate and the negative electrode plate, and the separator is completely soaked by the electrolyte.
9. The aqueous organic zinc ion battery according to claim 8, characterized in that: The aqueous organic zinc ion battery is a multi-layer structure, which comprises from top to bottom: a negative electrode shell, a negative electrode plate, a separator, a positive electrode plate, a gasket, a washer, and a positive electrode shell.
10. The aqueous organic zinc ion battery according to claim 8, characterized in that: The electrolyte is selected from one or more of zinc sulfate solution, zinc trifluoromethanesulfonate solution or zinc chloride solution.
Citation Information
Patent Citations
Novel compound, charge transport material, and organic device
CN103502252A
Electrically conductive adhesive composition
CN106574164A
Aqueous zinc ion battery and positive electrode preparation method
CN112614985A
Electrode and battery using same
CN1411084A
Benzoxazinophenoxazine compound, organic electroluminescent element material, and organic electroluminescent element hole transport material
JP2020111534A